Relics of the pre-script and script sites of Sapit Village: Evidence of the identity of Lombok’s civilization - Jannata Jannata; M. Gunawan Supiarmo (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2023)
Sapit is a village rich in natural resources and the hospitality of its people. This village is also rich in cultural diversity, not only in social norms, art, ideas, or notions but also in relics from pre-literate and script eras. The purpose of this research is to reveal information related to the legacy of the pre-script site and script of the village of Sapit as proof of the identity of the Lombok people's civilization. This study used a descriptive-qualitative method through the data collection stage through observation, data analysis, and data interpretation. The results showed that the heritage sites of the pre-literate Sapit village included punden, menhirs, dolmens, sarcophagi, beads, lisung stones, and statues in the form of creatures. Furthermore, cultural heritage is scriptural heritage, consisting of Sapit inscriptions, Langgar Pusaka, statues of Dewi Sri, ancient manuscripts or Korans, and kentongan. The existence of these heritage sites is strong evidence that Lombok has a cultural heritage that is unique or identifies it both nationally and globally.   Sapit merupakan desa yang kaya akan sumber daya alam, dan keramahtamahan masyarakatnya. Desa ini juga kaya akan keanekaragaman budaya, tidak hanya berupa norma sosial, seni, ide atau gagasan, melainkan peninggalan-peningalan zaman pra aksara dan aksara. Tujuan penelitian ini adalah mengungkapkan informasi terkait peninggalan situs pra aksara dan aksara desa Sapit sebagai bukti identitas peradaban masyarakat Lombok. Penelitian ini menggunakan metode kualitatif deskriptif yang dilakukan melalui tahap pengumpulan data dengan melakukan observasi, tahap analisis data, dan tahap interpretasi data. Hasil penelitian menunjukkan bahwa situs peninggalan desa Sapit zaman pra aksara, antara lain punden, menhir, dolmen, sarkofagus, manik-manik, lisung batu, dan arca berbentuk makhluk. Selanjutnya warisan budaya berupa peninggalan aksara, terdiri atas prasasti Sapit, Langgar Pusaka, arca Dewi Sri, mushaf atau al-Quran kuno, dan kentongan. Adanya situs peninggalan tersebut merupakan bukti kuat bahwa Lombok memiliki warisan budaya yang menjadi keunikan atau identitas baik secara nasional maupun global.